Menuju Lansia Sehat Bugar Jiwa Raga dengan Kombinasi Program S-CREEM KETAN, PENTOL, dan YOJASUKE - Suwanti; Liyanovitasari; Wulansari (UNIVERSITAS NGUDI WALUYO, 2024)
The large number of hypertension sufferers in Krajan Village, the low level of health screening for the elderly, the lack of health education related to hypertension in the elderly can influence delays in treating hypertension and even lead to the risk of uncontrolled hypertension. This can increase the risk of complications such as stroke. The aim of this community service is to increase the literacy and skills of the elderly regarding the management of hypertension through a combination of the S-CREEM KETAN (Health Care Community Screening), PENTOL (Cultivation of Toga for the Elderly) and YOJASUKE (Yoga and Walking) programs to achieve mental health, fitness for the elderly. This program is in accordance with the partners' vision, namely improving the health welfare of the elderly. Service methodology through Community-Based Participatory Research (CBPR). The activity consists of four stages: The first stage, health screening includes checking blood pressure, checking body height, checking random blood sugar, and checking body composition with the TANITA scale. The second stage, education regarding the benefits of Moringa leaves and planting Moringa trees. The third stage, training yoga chairs for the elderly. The fourth stage, a relaxing healthy walk. A total of 20 elderly people were actively involved in the activities. The results obtained from this combination of activities can increase elderly people's literacy based on measurement use questionaire and surve about the importance of health screening, increase literacy about the benefits of Moringa leaves, have knowledge and yoga chair skills and be able to do healthy walking. The conclusion from this service activity is that there is an increase in the literacy and skills of the elderly in knowledge and management of hypertension. ABSTRAK Banyaknya penderita hipertensi di Dusun Krajan, rendahnya skrining kesehatan pada lansia, minimnya pendidikan kesehatan terkait penyakit hipertensi pada lansia dapat mempengaruhi keterlambatan dalam penanganan hipertensi dan bahkan akan beresiko ke hipertensi tidak terkontrol. Hal ini dapat meningkatkan resiko ke komplikasi seperti stroke. Tujuan dari pengabdian masyarakat ini adalah meningkatkan literasi dan ketrampilan lansia tentang penanganan hipertensi melalui kombinasi program S-CREEM KETAN (Screening Masyarakat Peduli Kesehatan), PENTOL (Penanaman Toga untuk Lansia) dan YOJASUKE (Yoga dan Jalan Sehat Santai) untuk mencapai lansia sehat bugar jiwa dan raga. Program ini sesuai dengan visi mitra yaitu meningkatkan kesejahteraan kesehatan lansia. Metodologi pengabdian melalui Community-Based Participatory Research (CBPR). Kegiatan terdiri dari empat tahap: Tahap pertama, skrining kesehatan meliputi cek tekanan darah, cek tinggi badan, cek gula darah sewaktu, dan cek body composition dengan timbangan merk TANITA. Tahap kedua, edukasi pengenalan manfaat daun kelor dan penanaman pohon kelor. Tahap ketiga, melatih yoga chair pada lansia. Tahap keempat, jalan sehat santai. Sebanyak 20 lansia dilibatkan aktif dalam kegiatan. Hasil yang didapatkan dengan kegiatan kombinasi tersebut lansia bisa mengalami peningkatan literasi berdasarkan pengukuran dengan kuesioner dan survei tentang pentingnya skrining kesehatan, meningkatnya literasi tentang manfaat daun kelor, memiliki pengetahuan dan ketrampilan yoga chair serta mampu melakukan jalan sehat. Kesimpulan dari kegiatan pengabdian ini adanya peningkatan literasi dan ketrampilan lansia dalam pengetahuan dan penanganan hipertensi.